2007
DOI: 10.1007/s11103-007-9193-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of expressed sequence tags (ESTs) from subtracted cDNA libraries of Pennisetum glaucum seedlings

Abstract: Pearl millet (Pennisetum glaucum), used as forage and grain crop is a stress tolerant species. Here we identify differentially regulated transcripts in response to abiotic (salinity, drought and cold) stresses from subtracted cDNA libraries by single-pass sequencing of cDNA clones. A total of 2,494 EST sequences were clustered and assembled into a collection of 1,850 unique sequences with 224 contigs and 1,626 singleton sequences. By sequence comparisons the putative functions of many ESTs could be assigned. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 74 publications
0
44
0
1
Order By: Relevance
“…HG516611-HG517355. These EST sequences from the subtracted cDNA library are rich sources of drought stress-related genes that can help in understanding the molecular basis of drought tolerance in pearl millet by revealing a major part of the stress-responsive transcriptome (Mishra et al 2007). More than 25 % of the ESTs generated were classified into response to abiotic stimulus category.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HG516611-HG517355. These EST sequences from the subtracted cDNA library are rich sources of drought stress-related genes that can help in understanding the molecular basis of drought tolerance in pearl millet by revealing a major part of the stress-responsive transcriptome (Mishra et al 2007). More than 25 % of the ESTs generated were classified into response to abiotic stimulus category.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various methods for differential transcriptome analysis, Suppression Subtractive Hybridization (SSH) proves to be an efficient approach to isolate and identify cDNAs of differentially expressed genes in the absence of sequence information (Mishra et al 2007;Almeida et al 2013;Ding et al 2014;Khan et al 2014). In this technique differentially expressed genes can be normalized and enriched over 1000-fold in a single round of hybridization (Diatchenko et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation and cloning of PgHsc70 cDNA clone One of the EST clones (CD726670) from P. glaucum heat stress-responsive EST database (Mishra et al 2007) that showed maximum homology to PgHsc70 gene was used as a DNA probe for screening the Pennisetum subtractive heat stress cDNA library by the plaque hybridization method. The positive plaques were separated and DNA samples prepared for sequencing analysis (Reddy et al 2008a).…”
Section: Cdna Library Constructionmentioning
confidence: 99%
“…other genes in response to stress (Mishra et al 2007 12 Table 3. Relationships in predicted gene interaction network of drought resistance in almond.…”
mentioning
confidence: 99%